SERAC1 deficiency causes complicated HSP: evidence from a novel splice mutation in a large family. Issue 1 (15th September 2017) - Roeben, Benjamin; Schüle, Rebecca; Ruf, Susanne; Bender, Benjamin; Alhaddad, Bader; Benkert, Tanja; Meitinger, Thomas; Reich, Selina; Böhringer, Judith; Langhans, Claus-Dieter; Vaz, Frédéric M; Wortmann, Saskia B; et al.
Abstract : Objective: To demonstrate that mutations in the phosphatidylglycerol remodelling enzyme SERAC1 can cause juvenile-onset complicated hereditary spastic paraplegia (cHSP) clusters, thus adding SERAC1 to the increasing number of complex lipid cHSP genes. Methods: Combined genomic and functional validation studies (whole-exome sequencing, mRNA, cDNA and protein), biomarker investigations (3-methyl-glutaconic acid, filipin staining and phosphatidylglycerols PG34:1/PG36:1), and clinical and imaging phenotyping were performed in six affected subjects from two different branches of a large consanguineous family. Results: 5 of 6 affected subjects shared cHSP as a common disease phenotype. Three subjects presented with juvenile-onset oligosystemic cHSP, still able to walk several miles at age >10–20 years. This benign phenotypic cluster and disease progression is strikingly divergent to the severe infantile phenotype of all SERAC1 cases reported so far. Two family members showed a more multisystemic juvenile-onset cHSP, indicating an intermediate phenotype between the benign oligosystemic cHSP and the classic infantile SERAC1 cluster. The homozygous splice mutation led to loss of the full-length SERAC1 protein and impaired phosphatidylglycerol PG34:1/PG36:1 remodelling. These phosphatidylglycerol changes, however, were milder than in classic infantile-onset SERAC1 cases, which might partially explain the milder SERAC1 phenotype. Conclusions: Our findings add SERAC1 to the increasing list of complex lipid cHSP genes. At the same time they redefine the phenotypic spectrum of SERAC1 deficiency. It is associated not only with the severe infantile-onset 'Methylglutaconic aciduria, Deafness, Encephalopathy, Leigh-like' syndrome (MEGDEL syndrome), but also with oligosystemic juvenile-onset cHSP as part of the now unfolding SERAC1 deficiency spectrum.